Re-Naturing Cities: Evaluating the effects on future air quality in the city of Porto. (1st February 2020) - Rafael, S.; Augusto, B.; Ascenso, A.; Borrego, C.; Miranda, A.I.
Abstract: The effect of different "green" measures, such as the increase of urban green areas, the application of green roofs and the increase of surfaces albedo on urban air quality were evaluated with the WRF-CHIMERE modelling system. In order to account for the heterogeneity of urban areas, a single layer urban canopy model was coupled to the WRF model. The case study consists of a heat wave occurring in the Porto (Portugal) urban area in a future climate scenario, considering the Representative Concentration Pathway RCP8.5. The influence of the selected measures on PM10, NO2 and O3 concentrations was quantified and compared with a control run (without measures) simulation scenario. The results revealed that all the measures are able to mitigate the effects of heat waves by reducing the air temperature between −0.5 °C and −1 °C (maximum differences for the mean of the episode). Positive and negative effects were found in terms of air quality. The implementation of green roofs and the increase of surfaces albedo promoted an overall increase of PM10 (between +0.6% and +1.5%) and NO2 (between +0.8% and 3.5%) concentrations, which are closely related to a decrease of vertical mixing in the urban boundary layer. The increase of green urban areas promoted an overall decrease (on average) of both PM10 and NO2, by around −1% and −3%, respectively. The O3 levels increased with the increase of urban green areas, mostly located over the Porto urban area. Slight differences were promoted by the implementation of green roofs. For the increase of surfaces albedo, both increases and decreases of O3 concentrations were observed. The obtained results contribute to the knowledge of the chemical composition of the urban atmosphere and can be of great importance for stakeholders and decision-makers to deal with climate change impacts. Highlights: Cities must become resilient to be able to deal with future air pollution. Different "green" measures were studied using the WRF-CHIMERE modelling setup. Green roofs, white roofs and white surfaces increases PM10 and NO2 concentrations. Green urban areas decreases PM10 and NO2 concentrations and increases O3 levels. Double effects were found, showing the need of knowledge-based urban planning.